Review of Islamic Criminal Law on the Crime of Blasphemy (Case Study in Tebing Tinggi City) - Rambe, Choirul Hamdan; Mukhsin, Abdul (LEGAL BRIEF, 2024)
Freedom of religion is a human right that must be respected. In accordance with Article 28e, Paragraphs 1 and 2, of the 1945 Constitution, the Indonesian state provides freedom of religion and constitutional guarantees to its citizens. Social interaction is increasingly limitless due to the rapid development of technology and information. Currently, there are still many crimes committed through social media—also known as cyberspace—which are carried out via the internet. This includes online fraud, online prostitution, pornography, defamation, and even posting words that are hate speech in a religious context, namely blasphemy. One type of behavioral deviation and criminal act that is included in the realm of ethnicity, religion, race, and inter-group (SARA) is blasphemy. This study aims to collect reviews of Islamic criminal law regarding the violation of blasphemy in Tebing Tinggi. This study was conducted using normative legal research methods or library research. Primary and secondary data are the data sources used. In this study, the data collection used is documentation, which means facts and data contained in the text of laws or books related to the subject that has been examined by the author. This study found that, in Islamic criminal law, the crime of blasphemy can be likened to the crime of riddah and is punished according to the punishment of riddah, namely murder. On the other hand, in Indonesia, positive law also regulates blasphemy, especially Article 156a (KUHP), which stipulates that the legal sanction for perpetrators of blasphemy is a five-year prison sentence